Light intensity correction for quartz-enhanced photoacoustic spectroscopy using photothermal baseline - Chen, Xiang; Hu, Mai; Liu, Hao; Yao, Lu; Xu, Zhenyu; Kan, Ruifeng (Frontiers in Physics, 2022)
A convenient method of light intensity correction for quartz-enhanced photoacoustic spectroscopy (QEPAS) using photothermal baseline is demonstrated. The laser beam passes through the prongs of the quartz tuning fork (QTF) and then focused on the root of the prongs. First harmonic (1f) analysis is utilized to process the simultaneously induced photoacoustic and photothermal signals. The optical path length for photothermal spectroscopy is minimized to millimeter level, yielding negligible gas absorption. The demodulated 1f signal can be regarded as the superposition of the photoacoustic signal and the non-absorption photothermal baseline. A good linear relationship (R2=0.999) is observed between amplitude of photothermal baseline and light intensity. QEPAS signal normalized by photothermal baseline shows a good immunity to light intensity variation. An excellent linear response between normalized QEPAS signal and gas concentration is achieved. According to the Allan deviation analysis, the minimum detection limit for CH4 is 0.31 ppm at an integration time of 1200 s. With this strategy, the precise gas concentration and accurate light intensity of a QEPAS system can be simultaneously obtained with only a single QTF. Compared with the light intensity correction using a photodetector or a power meter, this method entails a low cost and small footprint. It is promising to mitigate the influence from light intensity drift in long-term field measurement of QEPAS systems.